IL11RA‐related Crouzon‐like autosomal recessive craniosynostosis in 10 new patients: Resemblances and differences. Issue 3 (23rd July 2018) - Brischoux‐Boucher, E.; Trimouille, A.; Baujat, G.; Goldenberg, A.; Schaefer, E.; Guichard, B.; Hannequin, P.; Paternoster, G.; Baer, S.; Cabrol, C.; Weber, E.; Godfrin, G.; et al.
Abstract : By describing 10 new patients recruited in centres for Human Genetics, we further delineate the clinical spectrum of a Crouzon‐like craniosynostosis disorder, officially termed craniosynostosis and dental anomalies (MIM614188). Singularly, it is inherited according to an autosomal recessive mode of inheritance. We identified six missense mutations in IL11RA, a gene encoding the alpha subunit of interleukin 11 receptor, 4 of them being novel, including 2 in the Ig‐like C2‐type domain. A subset of patients had an associated connective tissue disorder with joint hypermobility and intervertebral discs fragility. A smaller number of teeth anomalies than that previously reported in the two large series of patients evaluated in dental institutes points toward an ascertainment bias. Abstract : By describing 10 new patients recruited in centers for Human Genetics, we further delineate the clinical spectrum of a Crouzon‐like craniosynostosis disorder, officially termed craniosynostosis and dental anomalies (MIM614188). Singularly, it is inherited according to an autosomal recessive mode of inheritance. We identified six missense mutations in IL11RA, a gene encoding the alpha subunit of interleukin 11 receptor, 4 of them being novel, including 2 in the Ig‐like C2‐type domain.